(untitled) (International Journal of Engineering and Computer Science, 2023)
This research paper explores the implementation and benefits of Software-in-the-Loop (SIL) setups for testing motor controllers within virtual vehicle environments. SIL testing offers significant advantages in terms of cost, efficiency, and safety compared to traditional hardware-based testing methods. This paper discusses the key components of SIL setups, their implementation strategies, and case studies demonstrating their effectiveness in real-world applications. Additionally, challenges and future research directions in SIL testing for motor controllers are also addressed.